Ablation of paroxysmal atrial fibrillation using a second‐generation cryoballoon catheter or contact‐force sensing radiofrequency ablation catheter: A comparison of costs and long‐term clinical outcomes. (21st November 2017) - Yokokawa, Miki; Chugh, Aman; Latchamsetty, Rakesh; Ghanbari, Hamid; Crawford, Thomas; Jongnarangsin, Krit; Cunnane, Ryan; Saeed, Mohammed; Hornsby, Kyle; Krishnasamy, Kavita; Lohawijarn, Watchara; Keast, Robert; et al.
Abstract: Introduction: Although noninferiority of cryoballoon ablation (CBA) and radiofrequency catheter ablation for antral pulmonary vein isolation (APVI) has been reported in patients with paroxysmal atrial fibrillation (PAF), it is not clear whether contact force sensing (CF‐RFA) and CBA with the second‐generation catheter have similar procedural costs and long‐term outcomes. The objective of this study is to compare the long‐term efficacy and cost implications of CBA and CF‐RFA in patients with PAF. Methods and results: A first APVI was performed in 146 consecutive patients (age: 63 ± 10 years, men: 95 [65%], left atrial diameter: 42 ± 6 mm) with PAF using CBA (71) or CF‐RFA (75). Clinical outcomes and procedural costs were compared. The mean procedure time was significantly shorter with CBA than with CF‐RFA (98 ± 39 vs. 158 ± 47 minutes, P < 0.0001). Despite a higher equipment cost in the CBA than the CF‐RFA group, the total procedure cost was similar between the two groups (P = 0.26), primarily driven by a shorter procedure duration that resulted in a lower anesthesia cost. At 25 ± 5 months after a single ablation procedure, 51 patients (72%) in the CBA, and 55 patients (73%) in the CF‐RFA groups remained free from atrial arrhythmias without antiarrhythmic drug therapy (P = 0.84). Conclusions: The procedure duration was approximately 60 minutes shorter with CBA than CF‐RFA. The procedural costs were similar with both approaches. At 2 years after a single procedure, CBA and CF‐RFA have similar single‐procedure efficacies of 72–73%.